Analisis Strategi Marketing Pada Pembiayaan KPRS di Bank Muamalat Kantor Cabang Stabat - Ahmad Dahrul Dalimunthe; Waizul Qarni (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This study examines the implementation of the marketing strategy for Sharia KPR Bank Muamalat Stabat Branch and the challenges it faces. In this study, primary and secondary data from interviews, observations, and documentation were used in descriptive analysis techniques. The results of the study show that Bank Muamalat disseminates information through various mass media, both print (daily newspapers and magazines) and electronic (radio and television). Billboards, a type of outdoor advertising used by Bank Muamalat, are seen as a good tool to promote outreach.